1990
DOI: 10.1111/j.1559-1816.1990.tb01512.x
|View full text |Cite
|
Sign up to set email alerts
|

The Biological Findings in Post‐Traumatic Stress Disorder: A Review1

Abstract: In this paper the authors review the literature on biological and treatment studies of post‐traumatic stress disorder (PTSD) and present current unifying hypotheses regarding the pathophysiology. The psychophysiological studies stress overarousal, while endocrine studies suggest a decreased Cortisol production in denial and low symptom states with increases in highly symptomatic states. Suggestive evidence is provided that PTSD is associated with permanent changes in brain mechanisms involving the locus coerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…For example, Falger et al (1992) found that WWII Dutch Resistance veterans, compared with recent surgical and heart patients, had greater cardiovascular risk. On the basis of a combination of these and related findings (e.g., Orr, Pitman, Lasko, & Herz, 1993) and on our hidden variable conceptualization of military service, we propose that the heightened physiological reactivity that often results from combat exposure (e.g., Orr, 1990;ver Ellen & Van Kammen, 1990) may be associated with an increased risk of cardiovascular diseases in later life among combat veterans. One implication of this is that the declining association between Type A behavior and coronary heart disease (e.g., Miller, Turner, Tindale, Posavac, & Dugoni, 1991) might be an artifact of the decreasing proportion of veterans, especially those exposed to combat, in more recent studies.…”
Section: Combat Exposure and Physical Healthmentioning
confidence: 88%
“…For example, Falger et al (1992) found that WWII Dutch Resistance veterans, compared with recent surgical and heart patients, had greater cardiovascular risk. On the basis of a combination of these and related findings (e.g., Orr, Pitman, Lasko, & Herz, 1993) and on our hidden variable conceptualization of military service, we propose that the heightened physiological reactivity that often results from combat exposure (e.g., Orr, 1990;ver Ellen & Van Kammen, 1990) may be associated with an increased risk of cardiovascular diseases in later life among combat veterans. One implication of this is that the declining association between Type A behavior and coronary heart disease (e.g., Miller, Turner, Tindale, Posavac, & Dugoni, 1991) might be an artifact of the decreasing proportion of veterans, especially those exposed to combat, in more recent studies.…”
Section: Combat Exposure and Physical Healthmentioning
confidence: 88%
“…or induced by stress can be viewed as reflecting a dysregulation of the LHPA system Heim, Ehlert, & Hellhammer, 2000! and they have been associated with distinct emotional regulation problems~Checkley , 1996;Gunnar, 2001;Tobin, 2001;ver Ellen & Van Kammen, 1990!. Second, individual differences in normative cortisol levels have been linked to specific affect-related behaviors.…”
Section: Lhpa Emotional Dysregulation and Psychopathologymentioning
confidence: 99%
“…hormonal activity and abnormalities of the activation or inhibition of hormonal levels after a stressor~reactive!, has been linked to a variety of affective psychiatric disorders. Major depressive disorder and posttraumatic stress disorder are among the psychopathological disorders associated with LHPA abnormalities~Checkley, 1996;Gunnar, 2001;Tobin, 2001;ver Ellen & Van Kammen, 1990!. A common interpretation of these findings is that a dysfunctional LHPA system may result in extreme physiological activation during possible stressful situations or elevated activation during day to day activities.…”
Section: Lhpa Emotional Dysregulation and Psychopathologymentioning
confidence: 99%
“…There have been three randomized clinical trials with tricyclic antidepressants involving 124 patients, as well as numerous case reports and open trials 36 . Results have been mixed and generally modest in magnitude.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%